Style and dialogue in the stories of Fouad Al-Takarli A study in critical criticism (Journal of the College of Basic Education, 2022)
It must be in every literature work particularly in the field of the story includes manner and dialogue. Where the writer sets out by them in extension this work towards larger horizons and more comprehensive. In the way of manner is considered the base that narrator and utter tongue for his work , since without manner there is no story , because it was structured on it , it takes from it strength and reaction As for the dialogue is necessary mechanism within story work alike if it was utter or silent and this completely depends on individuals of the story and range of skillfulness for this mechanism and dexterity to do it . So the manner and dialogue are two aspects indispensable absolutely in story or novel too It is possible to build every technique of them separately according to view of the narrator , his point of view , his creative abilities , his artful skills and his artistic talents which he tries to convey them to the receipt easily and readily